Application of hyperthermia induced by superparamagnetic iron oxide nanoparticles in glioma treatment - Silva AC (Dove Medical Press, 2011)
André C Silva1, Tiago R Oliveira1,2, Javier B Mamani1, Suzana MF Malheiros3,4, Luciana Malavolta1, Lorena F Pavon1, Tatiana T Sibov1, Edson Amaro Jr1,5, Alberto Tannús6, Edson LG Vidoto6, Mateus J Martins6, Ricardo S Santos6, Lionel F Gamarra11Instituto Israelita de Ensino e Pesquisa Albert Einstein, IIEPAE, São Paulo, Brazil; 2Instituto de Física, Universidade de São Paulo, São Paulo, Brazil; 3Departament of Neurology and Neurosurgery, Universidade Federal de São Paulo, São Paulo, Brazil; 4Neuro-Oncology Program of Hospital Israelita Albert Einstein, São Paulo, Brazil; 5Instituto de Radiologia, Faculdade de Medicina; 6CIERMag-Instituto de Física de São Carlos, Universidade de São Paulo, São Paulo, BrazilAbstract: Gliomas are a group of heterogeneous primary central nervous system (CNS) tumors arising from the glial cells. Malignant gliomas account for a majority of malignant primary CNS tumors and are associated with high morbidity and mortality. Glioblastoma is the most frequent and malignant glioma, and despite the recent advances in diagnosis and new treatment options, its prognosis remains dismal. New opportunities for the development of effective therapies for malignant gliomas are urgently needed. Magnetic hyperthermia (MHT), which consists of heat generation in the region of the tumor through the application of magnetic nanoparticles subjected to an alternating magnetic field (AMF), has shown positive results in both preclinical and clinical assays. The aim of this review is to assess the relevance of hyperthermia induced by magnetic nanoparticles in the treatment of gliomas and to note the possible variations of the technique and its implication on the effectiveness of the treatment. We performed an electronic search in the literature from January 1990 to October 2010, in various databases, and after application of the inclusion criteria we obtained a total of 15 articles. In vitro studies and studies using animal models showed that MHT was effective in the promotion of tumor cell death and reduction of tumor mass or increase in survival. Two clinical studies showed that MHT could be applied safely and with few side effects. Some studies suggested that mechanisms of cell death, such as apoptosis, necrosis, and antitumor immune response were triggered by MHT. Based on these data, we could conclude that MHT proved to be efficient in most of the experiments, and that the improvement of the nanocomposites as well as the AMF equipment might contribute toward establishing MHT as a promising tool in the treatment of malignant gliomas.Keywords: brain tumor, magnetic hyperthermia, magnetic nanoparticle